(untitled) (Vietnam Journal of Community Medicine, 2022)
Background: Prophylactic antibiotics during cesarean section have been shown to be beneficial in reducing infection in women at high risk (in labor after rupture of membranes), or at low risk (not yet in labor and with membranes). A single dose of antibiotic prior to skin incision is as effective as multiple doses of antibiotics given intraoperatively and reduces the risk of infection by more than 50%, length of hospital stay and cost savings. Methods: A prospective, cross-sectional study of 337 cesarean section patients using prophylactic antibiotics at Ca Mau Obstetrics and pediatrics hospital from June 2019 to June 2020. Results: The study recorded the age from 18 to 46 years old; 53.2% of children compared; 53.7% of pregnant women did not have tuberous incisions; 56.7% of women with ectopic pregnancy from 37-40 weeks; 67.7% of women with ectopic pregnancy during labor; 21.4% of women used prophylatic antibiotics dose 2; 14.6% of women switched to antibiotics after using prophylatic antibiotics; 62% hospitalized for less than 5 days; 99.4% of women did not have surgical site infection. Conclusions: Prophylactic antibiotics reduce the risk of wound infection and length of hospital stay.